Sequence analysis of RNA-dependent RNA polymerase and development of a TaqMan real-time RT-PCR assay for detection of Macrobrachium rosenbergii nodavirus in giant freshwater prawns - Mohammadi, Zeinabsadat (2012)
The study presented in this thesis was mainly aimed to establish a novel Taq-Man based realtime RT-PCR assay for the detection of Macrobrachium rosenbergii nodavirus (MrNV) which is known to be implicated in the development of a fatal disease, called white tail disease (WTD) in giant freshwater prawns. A recombinant plasmid (R2-A) carrying a 650 bp fragment of the RNA2 of MrNV was constructed and used in the development of the assay. The newly established TaqMan real time RT-PCR method was 10 times more sensitive than the conventional RT-PCR assay and the results obtained from the intra-assay and the interassay showed the reproducibility of the assay. The PCR efficiency was calculated to be 99.6%. The developed primers and the TaqMan probe were shown to be specific to MrNV as they gave negative results to other viruses: extra small virus, (XSV), infectious hypodermal and hematopoietic necrosis virus (IHHNV) and Taura syndrome virus (TSV) which may also cause diseases in the giant freshwater prawn. Subsequent to the promising observations and results obtained from the newly established assay based on the plasmid R2-A, positive results were also obtained when the same assay was applied on field samples of WTD infected prawns. Determination of the whole sequence of the RNA dependent RNA polymerase of RNA1 in the Malaysian nodavirus strain was the other objective of this study. To this end, the presence of the virus in some tissues such as tail, body and gill was detected by RT-PCR using specific primers. The sequences of the inserts were determined and compared with those from the GenBank. The product size of the whole sequence of RNA1 was about 3199 bp and the Malaysian strain was shown to have the highest similarity (96%) to that of AY231436.2.